China's Direct Investment in the Russian Soybean Market in the Context of Risk Management Strategy - Yubo , Wang (Journal of Ecohumanism, 2024)
This article is based on the multifaceted impact factors of China's direct foreign investment in the Russian soybean market, identifying potential risks encountered in the investment process, including political, economic, logistics and supply chain, socio-cultural, and environmental risks. On the basis of these risks, the paper proposes a comprehensive set of risk management measures, and validates the effectiveness and practicality of these risk mitigation strategies through the analysis of successful investment cases. Overall, the paper underscores the significance of comprehensive risk management for sustainable development, providing systematic and comprehensive risk management advice for Chinese enterprises engaged in direct investments in the Russian soybean market